Aumento na ingestão de sódio durante as fases pós-natais induz aumento de pressão arterial na fase adulta - Moreira, Marina Conceição dos Santos (2014)
Changes in plasma sodium concentration have led to adjustment mechanisms in order to restore their physiological conditions. The behavioral adjustments consist in the regulation of water and sodium intake. Among the vegetative adjustments, we highlight changes in renal sympathetic activity, blood pressure, renal blood flow (RBF) and renal vascular conductance (RVC). Experimental evidence has demonstrated increase of blo od pressure of the adult offspring from mothers with high sodium diets during pregnancy. Although these studies had demonstrated the importance of prenatal phases in hypertension development, there has been no evidence of the effects of high sodium diets during postnatal phases in relation to hypertension. Thus, in the present study, we evaluated the effects of sodium overload during childhood on cardiovascular and behavioral parameters in adulthood. That way, 21 days after birth, we have offered to the experimental group, hypertonic solution (NaCl 0.3 M) and food ad libitum for 60 days. The control rats were maintained with tap water and food ad libitum. Afterwards, both groups were maintained with tap water and food during 15 days (recovery). Later, we per formed chronic cannulation of right femoral artery to record baseline mean arterial pressure (MAP) and heart rate (HR) in unanesthetized animals. In the experimental group, we observed increases in basal MAP (118.3 ± 2.7 mmHg) and HR (398.2 ± 7.5 bpm), compared with the control group (98.6 ± 2.6 mmHg; 365.4 ± 12.2 bpm). Baroreflex index was diminished in experimental group in relation to control group by phenylephrine infusions ( -1.24 ± 0.2 bpm·mmHg -1 vs. -1.83 ± 0.04 bpm·mmHg -1 , respectively) as by sodium nitroprusside infusions (0.85 ± 0.22 bpm·mmHg -1 vs. 2.12 ± 0.2 bpm·mmHg -1 , respectively). The baseline values of MAP, HR, RBF, RVC and renal sympathetic nerve activity (RSNA) in anesthetized animals were evaluated. MAP and HR of experimental group (124.4 ± 3.0 mmHg; 437.9 ± 10.5 bpm) were significantly higher than control group (102.4 ± 2.4 mmHg; 375.2 ± 15.4 bpm). The baseline values of RBF (control: 3.4 ± 0.4 ml·min -1 ; experimental: 3.9 ± 0.2 ml·min -1 ), RVC (control: 0.0288 ± 0.0044 ml·(min·mmHg) -1 ; experimental: 0.0336 ± 0.0012 ml·(min·mmHg) -1 ) and RSNA (control: 0.0300 ± 0.0095 V and 89.5 ± 3.67 spikes·s -1 ; experimental: 0.0351 ± 0.0109 V and 78.1 ± 4.89 spikes·s -1 ) were similar between the groups. Ex vivo cardiovascular function in adulthood was also evaluated. It has been observed that animals treated with sodium overload during the postnatal period showed reduction of vascular endothelium-independent relaxation and also an increase in intraventricular diastolic pressure during the cardiac reperfusion. Furthermore, after the recovery period, the animals were submitted to osmotic challenge. The cardiovascular adjustments induced by acute hypernatremia were evaluated. It was observed that in the control animals, the infusion of hypertonic saline evoked a transient increase in MAP (Δ 9.2 ± 2.2 mmHg ), transient bradycardia (Δ -18.9 ± 7.9 bpm) and sustained increases in RBF (Δ 37.7 ± 6.9 % of baseline ) and RVC (Δ 50.0 ± 4.4 % of baseline, 60 min after infusion). However, in the experimental rats, hypertonic saline infusion caused a transient increase in MAP, higher than observed in control animals (Δ 18. 7 ± 1.7 mmHg, after 10 min) and sustained bradycardia (Δ -25.0 ± 10.2 bpm, after 60 min). The increases in RBF (Δ 30.8 ± 11.0% of baseline, after 60 min) and RVC (Δ 27.9 ± 12.3 % of baseline, af ter 60 min) were lower than the observed in the control group. Later, we performed tests of water and sodium intake induced by furosemide (10 mg·kg -1 bw, sc). In test-induced drinking, the hypertonic 0.3 M sodium intake was reduced in experimental animals compared to the control group (7.8 ± 1.1 ml vs. 12.1 ± 0.6 ml, respectively). Alt ogether, the results of the present study show that changes in hidromineral homeostasis, in postuterine phases, affect the behavioral and cardiovascular adjustments induced by sodium depletion and hypernatremia. Furthermore, they show that a high -sodium diet during the postnatal period alters baroreflex sensitivity and BP, in adulthood, compromising the cardiac relaxation after ischemia and endothelium-independent vasorelaxation .